British Policy and Strategy in the Middle East in 1941: Three Wars ‘East of Suez’ - A. M. Fomin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
After the defeat of France in the summer of 1940, Great Britain was left face to face with the Nazi Germany. It managed to endure the ﬁrst act of the ‘Battle of Britain’, but could not wage a full-scale war on the continent. Under these conditions, the defense of the British positions in the Mediterranean and in the Middle East became a top priority for W. Churchill’s cabinet. The author examines three episodes of Great Britain’s struggle for the Middle East in 1941 (Iraq, Syria, Iran), framing them into the general logic of the German-British confrontation during this period.The author emphasizes that potential assertion of German hegemony in the Middle East could have made the defense of Suez almost impossible, as well as the communication with India, and would have provided the Reich with an access to almost inexhaustible supplies of fuel. Widespread antiBritish sentiments on the part of the local political and military elites could contribute greatly to the realization of such, catastrophic for Britain, scenario. Under these circumstances, the British government decided to capture the initiative. The paper examines the British military operations in Iraq and Syria. Special attention is paid to the complex dynamics of relations of the British cabinet with the Vichy regime and the Free France movement. As the author notes, the sharpest disagreements aroused on the future of Syria and Lebanon, and the prospects of granting them independence. In the Iran’s case, the necessity of harmonizing policies with the Soviet Union came to the fore. The growing German inﬂuence in the region, as well as the need to establish a new route for Lend-Lease aid to the USSR, fostered mutual understanding. After the joint Anglo-Soviet military operation in August-September 1941, Iran was divided into occupation zones. Finally, the paper examines the UK position with regard to the neutrality of Turkey. The author concludes that all these military operations led to the creation of a ‘temporary regime’ of the British domination in the Middle East. However, the Anglo-French and Anglo-Soviet rivalries had not disappeared and, compounded by the growing US presence in the region, laid basis for new conﬂicts in the post-war period.